Implementation of Disciplinary Penalties For Conditioners Who Violate The Rule of Order In Class I Penalty Institution In Surabaya - Lucky Dwikinanda Winduastiko; Asep Heri (Faculty of Law, Merdeka University Surabaya, Indonesia, 2023)
The implementation of disciplinary punishment for convicts who violate the order is based on Minister of Law and Human Rights Regulation No. 6 of 2013 concerning Rules of Correctional Institutions and State Detention Houses in Relation to Convict Development (Studies in Class I Correctional Institutions in Surabaya). The approach method used in this research is a juridical-sociological approach. From the results of this thesis research it is concluded that Administrative Sanctions for Correctional Families violate Article 4 of the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 6 of 2013, namely violations in the form of minor violations, moderate violations and serious violations. Applied to all Correctional Inmates in Correctional Institutions, with the aim of disciplinary punishment as a form of administrative sanction to improve and educate Correctional Inmates who commit disciplinary violations. Law enforcement is needed in handling violations of disciplinary regulations for Correctional Families. In practice, the procedures for implementing administrative sanctions for inmates of corrective correctional centers are focused on correctional officers who must be obliged to re-examine inmates in accordance with the flow of the mechanism for disciplinary violations, with the aim of finding out the violations that have been committed. In this case, the sense of justice and security in the correctional cell takes precedence. If a prisoner has committed an offense before, then the officer will provide appropriate sanctions and of course the sanctions given will be heavier than the disciplinary punishment ever imposed on him, but only only one sentence.